Does cognitive behavioural therapy for insomnia improve cognitive performance? A systematic review and narrative synthesis - Herbert, V; Kyle, S; Pratt, D (Elsevier, 2017)
Individuals with insomnia report difficulties pertaining to their cognitive functioning. Cognitive behavioural therapy for insomnia (CBT-I) is associated with robust, long-term improvements in sleep parameters, however less is known about the impact of CBT-I on the daytime correlates of the disorder. A systematic review and narrative synthesis was conducted in order to summarise and evaluate the evidence regarding the impact of CBT-I on cognitive functioning. Reference databases were searched and studies were included if they assessed cognitive performance as an outcome of CBT-I, using either self-report questionnaires or cognitive tests. Eighteen studies met inclusion criteria, comprising 923 individuals with insomnia symptoms. The standardised mean difference was calculated at post-intervention and follow-up. We found preliminary evidence for small to moderate effects of CBT-I on subjective measures of cognitive functioning. Few of the effects were statistically significant, likely due to small sample sizes and limited statistical power. There is a lack of evidence with regards to the impact of CBT-I on objective cognitive performance, primarily due to the small number of studies that administered an objective measure (n=4). We conclude that adequately powered randomised controlled trials (RCT), utilising both subjective and objective measures of cognitive functioning are required.